2020
DOI: 10.1002/nbm.4382
|View full text |Cite
|
Sign up to set email alerts
|

Improved depiction of subthalamic nucleus and globus pallidus internus with optimized high‐resolution quantitative susceptibility mapping at 7 T

Abstract: The subthalamic nucleus (STN) and globus pallidus internus (GPi) are commonly used targets in deep-brain stimulation (DBS) surgery for the treatment of movement disorders. The success of DBS critically depends on the spatial precision of stimulation. By taking advantage of good contrast between iron-rich deep-brain nuclei and surrounding tissues, quantitative susceptibility mapping (QSM) has shown promise in differentiating the STN and GPi from the adjacent substantia nigra and globus pallidus externus, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Whether the CNR measurements or ANT morphology observations based on QSM are applicable to the epilepsy population remains unclear. We have occasionally found the ATN to be clearly visible in young, healthy volunteers in figures from other studies using QSM to delineate the STN and GPi, even when using a lower spatial resolution than our study ( Liu et al, 2013 ; Dimov et al, 2018 ; Cong et al, 2020 ). Second, image motion artifacts can potentially occur during the scanning of conscious patients with tremors in this study, decreasing imaging quality.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Whether the CNR measurements or ANT morphology observations based on QSM are applicable to the epilepsy population remains unclear. We have occasionally found the ATN to be clearly visible in young, healthy volunteers in figures from other studies using QSM to delineate the STN and GPi, even when using a lower spatial resolution than our study ( Liu et al, 2013 ; Dimov et al, 2018 ; Cong et al, 2020 ). Second, image motion artifacts can potentially occur during the scanning of conscious patients with tremors in this study, decreasing imaging quality.…”
Section: Discussioncontrasting
confidence: 60%
“…However, in Yi Wang’s study using QSM for the depiction of STN, we found that the CNRs of the STN relative to the adjacent tissue were only decreased slightly on QSM when this image was resampled to 2-mm slice thickness from the original 0.5-mm isotropic resolution ( Dimov et al, 2018 ). In addition, the borders of the ANT are clearly visible on 3 T QSM with a spatial resolution of 0.75 × 0.75 × 2 mm or 0.75 × 0.75 × 1.5 mm, based on images from other studies ( Liu et al, 2013 ; Dimov et al, 2018 ; Cong et al, 2020 ). Fourth, the accuracy of QSM to delineate ANT was not completely defined, and the measurements were performed on patients in whom the ANT stimulation was not planned.…”
Section: Discussionmentioning
confidence: 93%
“…These diseases include hemorrhagic stroke, multiple sclerosis (MS), Alzheimer disease, Parkinson disease, amyotrophic lateral sclerosis, and tumors. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Particularly, QSM (1) enables differentiation between tissues that are paramagnetic (relative to water), including hemorrhages, and more diamagnetic than water, including calcifications, [16][17][18][19] and their quantification with additional R 2 or R * 2 mapping [20][21][22][23][24][25][26][27][28][29] and (2) improves anatomical visualization [30][31][32] and segmentation. 33,34 The latter has proven valuable for presurgical mapping of deep gray nuclei targets in deep brain stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, QSM (1) enables differentiation between tissues that are paramagnetic (relative to water), including hemorrhages, and more diamagnetic than water, including calcifications, 16–19 and their quantification with additional R 2 or R2*$$ {R}_2^{\ast } $$ mapping 20–29 and (2) improves anatomical visualization 30–32 and segmentation 33,34 . The latter has proven valuable for presurgical mapping of deep gray nuclei targets in deep brain stimulation 30,35–39 . QSM is also utilized to study imbalances in neurotransmitter levels or metabolism in psychiatric disorders such as psychosis 40,41 and depression 42,43 and to investigate neural mechanisms through which alcohol affects the brain 44–46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation